Prediction score for in-hospital mortality among patients with necrotizing fasciitis: derivation and internal validation - Kritnikornkul, Amornchai; Fanmoon , Panuwat; Jearwattanakanok , Kijja (Journal of Nakornping Hospital, 2023)
Background: Necrotizing fasciitis (NF) is a rapidly progressive, life-threatening skin and soft tissue infection. Currently, a risk score tool to predict in-hospital mortality in NF patients is not warranted. Objective: This study aimed to develop a tool to predict in-hospital mortality in NF patients. Material and Methods: A retrospective study was conducted during January 2019 to December 2020. The hospital records of 293 NF patients were reviewed. Data including age, sex, location of lesion, laboratory results, comorbidity, pathogen organism, and in-hospital mortality were collected. Multivariable binary regression with backward stepwise elimination was used to identify a set of prognostic factors, whose regression coefficients were weighed, assigned, and summed to a total risk score. Finally, three risk groups—low, moderate, and high—for in-hospital mortality in NF patients were classified. Results: A cohort of 293 patients diagnosed with NF was investigated, among whom 25 cases, accounting for 8.4% of in-hospital mortality. Four prognostic factors significantly associated with predicting in-hospital mortality were identified: diabetes mellitus (Adj. RR 3.18, 95% CI 1.05-9.68), cirrhosis (Adj. RR 7.40, 95% CI 4.18-13.09), leukocytosis exceeding 20,000/uL (Adj. RR 2.61, 95% CI 2.13-3.20), and blood lactate levels (Adj. RR 1.12, 95% CI 1.09-1.15). These factors exhibited the prediction for in-hospital mortality up to 91.3% (AuROC 91.3%, 95% CI 82.5-100.0). The Likelihood Ratio of a positive result for the low-risk (<5 points), moderate-risk (5-8 points), and high-risk (>8 points) groups were 0.18 (95% CI 0.05-0.67, p <0.001), 0.86 (95% CI 0.34-2.17, p=0.744), and 9.06 (95% CI 3.88-21.14, p <0.001), respectively. Conclusion: The developed risk scoring system in this study, consisting of four prognostic factors, demonstrates a high feasibility in assessing the ability to discriminate and predict mortality in NF patients. However, further validation of this tool should be conducted in tertiary and subsequent healthcare settings to ensure its accuracy and applicability.